The Effects of 3D Audio on Hologram Localization in Augmented Reality Environments. (September 2017) - Arce, Terek; Fuchs, Henry; McMullen, Kyla
Currently available augmented reality systems have a narrow field of view, giving users only a small window to look through to find holograms in the environment. The challenge for developers is to direct users' attention to holograms outside this window. To alleviate this field of view constraint, most research has focused on hardware improvements to the head mounted display. However, incorporating 3D audio cues into programs could also aid users in this localization task. This paper investigates the effectiveness of 3D audio on hologram localization. A comparison of 3D audio, visual, and mixed-mode stimuli shows that users are able to localize holograms significantly faster under conditions that include 3D audio. To our knowledge, this is the first study to explore the use of 3D audio in localization tasks using augmented reality systems. The results provide a basis for the incorporation of 3D audio in augmented reality applications.